German-Turkish Commodities Trade in Contrast to the Decline in German Foreign Trade - Maria V. Gracheva (Современная Европа)
The article examines the specifics of Germany's trade with Turkey in comparison with the characteristics of all-German foreign trade. The author shows the successful development of the Turkish direction of German foreign trade after 2010, the roles of Turkey and Germany as trading partners, and examines in detail the structure of bilateral trade. Structural changes are analysed on the basis of the electronic database of German Federal Statistical Office, which allows to use the statistics in three profiles – four product groups, thirty branches and 248 product items. Particular attention is paid to the changes that occurred in 2023. The unit costs of exports and imports by product groups are calculated and a significant difference in favor of Germany is revealed for the main product group – finished products. The main branches of export and import are identified and compared with analogous branches of all-German trade flows. Based on this comparison, the peculiar features of the Turkish export market (increased role of the automotive, mechanical engineering and chemical industries, the growing importance of the production of vehicles other than cars) and the import source (increased focus on the automotive, clothing and engineering industries) are formulated. Both the most important and the most promising individual commodity items in bilateral trade are identified (the first include aircraft for export and outerwear for import, the second include auto components and cars for import). The conclusions about the likely increase in the importance of imports from Turkey and the imminent entry of this country into the top ten trading partners of Germany are substantiated.